Процесуальні правовідносини в сфері вирішення трудових спорів - Шевченко, Д.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Анализируются процессуальные правоотношения по рассмотрению трудовых споров. Дается общее понятие процессуальных правоотношений по рассмотрению трудовых споров, раскрыты основные принципы, определяющие указанные правоотношения, дана сравнительная характеристика основных теорий деления процессуальных правоотношений по видам. Затронута проблема дальнейшего совершенствования законодательства в части законодательного закрепления понятия процессуальных правоотношений по рассмотрению трудовых споров. This article is given over to legal proceedings in the field of consideration of labor disputes. More specifically, the article explains the general notion of legal proceedings in the field of consideration of labor disputes, reveals general principles that determine the specified legal relations. Moreover, it is given a comparative analysis of basic theories concerning the legal proceedings breakdown by types. In addition the article touches on the aspects of successive legislation improvement in terms of legislative consolidation of legal proceedings in the field of consideration of labor disputes.